Effects of wheat gluten and plasma protein on growth performance and digestibility of nutrients in nursery pigs - J S Pendergraft; C G Mills; L L Burnham; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1993)
An experiment was conducted to determine the nutritional value of wheat gluten and spray-dried porcine plasma in diets for weanling pigs. For the experiment, 120 pigs (14 lb avg initial body wt) were used in a 35-d growth assay. Treatments fed from d 0 to 14 postweaning were: 1) a dried skim milk-dried whey-soybean mealbased control; and 2, 3, and 4) spray-dried wheat gluten, spray-dried porcine plasma, and a blend of the wheat gluten and porcine plasma used to replace dried skim milk on a protein basis. All pigs were fed the same corn-soybean meal-dried whey-based diet from d 14 to 35. For d 0 to 14, pigs fed porcine plasma protein had greater average daily gain and average daily feed intake than pigs fed wheat gluten. However, for d 14 to 21 (i.e., during the transition period to the phase II diet), pigs fed diets with wheat gluten had the greatest feed intake and rate of gain compared with pigs fed other protein sources during phase I. Overall, pigs fed diets with wheat gluten and(or) plasma protein had greater rates and efficiencies of gain than pigs fed dried skim milk. The results indicate that spray-dried porcine plasma protein improves growth rate for the initial postweaning phase; however, feeding spray-dried wheat gluten during phase I results in improved growth performance during the transition to a phase II diet.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Wheat gluten; Plasma protein; Growth; Digestibility; Nursery